Chemopreventive Effects of Whole Cranberry (Vaccinium macrocarpon) on Colitis‐Associated Colon Tumorigenesis. Issue 24 (23rd November 2018) - Wu, Xian; Song, Mingyue; Cai, Xiaokun; Neto, Catherine; Tata, Anuradha; Han, Yanhui; Wang, Qi; Tang, Zhonghai; Xiao, Hang
Abstract : Scope: There are growing interests in using a whole‐food‐based approach to prevent chronic diseases due to potential synergistic interactions among different bioactive components within the whole foods. North American cranberry ( Vaccinium macrocarpon ), a polyphenol‐rich fruit, has been shown to exert multiple beneficial health effects. Methods and results: For the first time, the protective effects of whole cranberry powder (WCP) are determined against colitis‐associated mouse colon tumorigenesis induced by azoxymethane (AOM) and dextran sulfate sodium (DSS). The results show that dietary administration of WCP (1.5%, w/w in the diet) significantly suppresses colon tumorigenesis as indicated by the reduced tumor incidence, multiplicity, burden, and average tumor size in WCP‐fed mice compared to the positive control mice. Both gene and protein expression levels of pro‐inflammatory cytokines IL‐1β, IL‐6, and TNF‐α are markedly attenuated by WCP treatment in the colon of AOM/DSS‐treated mice. Moreover, WCP profoundly modulates multiple signaling pathways/proteins related to inflammation, cell proliferation, apoptosis, angiogenesis, and metastasis in the colon, which is closely associated with the inhibitory effects of WCP on colon tumorigenesis. Conclusion: Overall, the results demonstrate chemopreventive effects of WCP on colon tumorigenesis in mice, providing a scientific basis for using the whole cranberry as a functional food to promote colon health in humans. Abstract : Dietary administration of whole cranberry is demonstrated to significantly suppress colonic tumorigenesis in vivo. Mechanistic investigation demonstrates that whole cranberry attenuates colitis‐associated colon tumorigenesis by suppressing PI3K/Akt/COX‐2 signaling, inducing phase II enzymes, and modulating key signaling proteins related to cell growth, angiogenesis, and metastasis.